2004
DOI: 10.3354/meps266077
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the green macroalga Enteromorpha intestinalis on macrobenthic and seagrass assemblages in a shallow coastal estuary

Abstract: A common symptom of eutrophication in temperate estuaries is the proliferation of ephemeral, floating macroalgae. Information on the effects of blooms on underlying assemblages mostly originates from non-vegetated intertidal and subtidal habitats. Blooms also often settle in large aggregations over seagrasses, where they decompose. To test hypotheses concerning the effect of dense mats on underlying assemblages of benthic invertebrates within a seagrass meadow, biomass of the green macroalga Enteromorpha intes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(36 citation statements)
references
References 64 publications
0
35
0
1
Order By: Relevance
“…The negative effects of macroalgal blooms on seagrasses have been documented in many areas of the world, such as Australia, Japan, America and Europe (e.g. Cummins et al, 2004;Huntington and Boyer, 2008;Martínez-Lüscher and Holmer, 2010;Sugimoto et al, 2007). Small-statured seagrass species are more impacted than larger species, and the effect is often proportional to the biomass of macroalgae (Thomsen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The negative effects of macroalgal blooms on seagrasses have been documented in many areas of the world, such as Australia, Japan, America and Europe (e.g. Cummins et al, 2004;Huntington and Boyer, 2008;Martínez-Lüscher and Holmer, 2010;Sugimoto et al, 2007). Small-statured seagrass species are more impacted than larger species, and the effect is often proportional to the biomass of macroalgae (Thomsen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…These processes have been associated with phytoplankton blooms, fish and other faunal kills, as well as seagrass declines (Buchsbaum et al 1991, Hauxwell et al 2001, Nedergaard et al 2002, Cummins et al 2004). The fate of macroalgal biomass deposited to the sediments, however, is less clear.…”
Section: Label Incorporation Into Bulk Sedimentsmentioning
confidence: 99%
“…The deleterious effects these blooms have on the surrounding system while alive and following die-off have been studied extensively (e.g. Sfriso et al 1992, Raffaelli 2000, Hauxwell et al 2001, Cummins et al 2004, Nuzzi & Waters 2004.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have identified levels of biomass at which, or above, significant harmful effects on biota have been, or may be, observed (e.g. Valiela et al, 1997;Ö sterling and Pihl, 2001;Cummins et al, 2004). Therefore, biomass values, whenever available, should reinforce the classification method and be used to turn results more accurate.…”
Section: Assessment Method: Option 1 Vs Optionmentioning
confidence: 99%